Evaluation of a short version of the Experiences in Close Relationships-Revised questionnaire (ECR-RD8): results from a representative German sample - Ehrenthal, Johannes C.; Zimmermann, Johannes; Brenk-Franz, Katja; Dinger, Ulrike; Schauenburg, Henning; Braehler, Elmar; Strauss, Bernhard (BMC Psychology, 2021)
Background Attachment insecurity is a prominent risk factor for the development and course of psychiatric and psychosomatic disorders. The Experiences in Close Relationships - Revised (ECR-R) questionnaire is a widely used self-report to assess attachment related anxiety and avoidance. However, its length has the potential to restrict its use in large, multi-instrument studies. The aim of this study was to develop and evaluate a brief version of the ECR-R, and provide norm values for the German population. Methods A screening version of the original ECR-R was developed through principal components analysis of datasets from several previous studies. In a representative sample of 2428 randomly selected individuals from the German population, we compared fit indices of different models by means of confirmatory factor analyses (CFA). We investigated the convergent validity of the screening version in an independent convenience sample of 557 participants. Correlations between the short and the full scale were investigated in a re-analysis of the original German ECR-R evaluation sample. Results CFA indicated a satisfactory model fit for an eight-item version (ECR-RD8). The ECR-RD8 demonstrated adequate reliability. The subscales correlated as expected with another self-report measure of attachment in an independent sample. Individuals with higher levels of attachment anxiety, but especially higher levels of attachment avoidance were significantly more likely to not be in a relationship, across all age groups. Correlations between the short and the full scale were high. Conclusions The ECR-RD8 appears to be a reliable, valid, and economic questionnaire for assessing attachment insecurity. In addition, the reported population-based norm values will help to contextualize future research findings.